1999
DOI: 10.1161/01.cir.100.25.2485
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Blunts Endotoxin-Induced Coagulation Activation

Abstract: Background-Lipopolysaccharide (LPS) is a major trigger of sepsis-induced disseminated intravascular coagulation (DIC) via the tissue factor (TF)/factor VIIa-dependent pathway of coagulation. Experimental endotoxemia has been used repeatedly to explore this complex pathophysiology, but little is known about the effects of clinically used anticoagulants in this setting. Therefore, we compared with placebo the effects of unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) on LPS-induced coagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
119
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 35 publications
9
119
0
3
Order By: Relevance
“…10 -12 Serum concentrations of antioxidants are low in patients with cardiovascular disease, 10 and high local concentrations of antioxidants such as vitamin C have been shown to restore endothelial function in patients with cardiovascular risk factors, including diabetes, hypertension, hypercholesterolemia, and smoking. 13 The purpose of the present study was to test the hypothesis that systemic concentrations of the antioxidant vitamin C are decreased during acute inflammation secondary to Escherichia coli endotoxin (LPS) and that endotoxin-associated endothelial dysfunction can be restored by high doses of vitamin C. The administration of low doses of LPS is an established model for generation of an acute systemic inflammatory response in humans, 5,14,15 and forearm vascular function was studied using strain-gauge plethysmography.…”
mentioning
confidence: 99%
“…10 -12 Serum concentrations of antioxidants are low in patients with cardiovascular disease, 10 and high local concentrations of antioxidants such as vitamin C have been shown to restore endothelial function in patients with cardiovascular risk factors, including diabetes, hypertension, hypercholesterolemia, and smoking. 13 The purpose of the present study was to test the hypothesis that systemic concentrations of the antioxidant vitamin C are decreased during acute inflammation secondary to Escherichia coli endotoxin (LPS) and that endotoxin-associated endothelial dysfunction can be restored by high doses of vitamin C. The administration of low doses of LPS is an established model for generation of an acute systemic inflammatory response in humans, 5,14,15 and forearm vascular function was studied using strain-gauge plethysmography.…”
mentioning
confidence: 99%
“…19 Injection of endotoxin similarly causes formation of large amounts of plasmin, with a maximum PPIC concentration after 2 hours. 20 In contrast to ancrod, endotoxin also stimulates tPA release from the endothelium. 20,21 The profibrinolytic response is subsequently terminated by increasing levels of PAI-1, 20,21 resulting in a rapid drop in PPIC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a consequence of the increased amount of soluble fibrin acting as cofactor in tPA-induced plasminogen activation and possibly shielding tPA from inactivation by PAI-1. Pernerstorfer at al 20 showed that maximal thrombin generation occurs 4 to 6 hours after endotoxin infusion. Levels of prothrombin fragment F1.2 and thrombinantithrombin complexes, as well as soluble fibrin, return to baseline within 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations